Effects of Itraconazole and Rifampin on the Pharmacokinetics of Mobocertinib (TAK‐788), an Oral Epidermal Growth Factor Receptor Inhibitor, in Healthy Volunteers. Issue 9 (19th June 2021) - Zhang, Steven; Jin, Shu; Griffin, Celina; Feng, Zhongling; Lin, Jianchang; Venkatakrishnan, Karthik; Gupta, Neeraj
Abstract: Mobocertinib (TAK‐788) is an investigational oral tyrosine kinase inhibitor targeting epidermal growth factor receptor and human epidermal growth factor 2. A phase 1 open‐label, 2‐period, fixed‐sequence, 2‐part study (NCT03928327) characterized effects of a strong CYP3A4 inhibitor (itraconazole) and inducer (rifampin) on the pharmacokinetics (PK) of mobocertinib and its active metabolites, AP32960 and AP32914. Healthy volunteers (n = 12 per part) received a single dose of mobocertinib alone (20 mg, part 1; 160 mg, part 2) and with multiple doses of itraconazole 200 mg once daily (part 1) or rifampin 600 mg once daily (part 2). Coadministration of itraconazole with mobocertinib increased the combined molar area under the plasma concentration‐time curve from time 0 to infinity (AUC0‐∞ ) of mobocertinib, AP32960, and AP32914 by 527% (geometric least‐squares mean [LSM] ratio, 6.27; 90% confidence interval [CI], 5.20‐7.56). Coadministration of rifampin with mobocertinib decreased the combined molar AUC0‐∞ of mobocertinib, AP32960, and AP32914 by 95% (geometric LSM ratio, 0.05; 90%CI, 0.04‐0.07). Based on these results, the strong CYP3A inhibitor itraconazole and inducer rifampin significantly influenced the PK of mobocertinib and its active metabolites. Coadministration of mobocertinib with moderate and strong CYP3A inhibitors or inducers is not recommended in ongoing clinical trials.